Silencing matrix metalloproteinase-13 (Mmp-13) reduces inflammatory bone resorption associated with LPS-induced periodontal disease in vivo - Guimaraes-Stabili, Morgana R. [UNESP]; de Medeiros, Marcell Costa [UNESP]; Rossi, Danuza [UNESP]; Camilli, Angelo Constantino [UNESP]; Zanelli, Cleslei Fernando [UNESP]; Valentini, Sandro Roberto [UNESP]; Spolidorio, Luis Carlos [UNESP]; Kirkwood, Keith Lough; Rossa, Carlos [UNESP] (Springer Nature, 2021)
Objectives: The aim of this study was to evaluate the effect of specific inhibition of MMP-13 on inflammation and inflammatory bone resorption in a murine model of lipopolysaccharide (LPS)-induced periodontitis. Materials and methods: Periodontitis was induced in mice by micro-injections of LPS into the gingival tissues adjacent to the palatal surfaces of maxillary molars twice a week for 15 days. Matrix metalloproteinase-13 (Mmp-13) shRNA or a specific biochemical inhibitor were also injected into the same sites in alternating days with the LPS injections. Efficacy of shRNA-mediated silencing of Mmp-13 was verified by quantitative real-time polymerase chain reaction (qPCR) and immunoblot. Bone resorption was assessed by microcomputed tomography (uCT). Histological sections stained with hematoxylin/eosin (H/E) were used in the stereometric analysis of the inflammatory infiltrate. Gingival tissues were used to evaluate expression of Mmp-13, Il-6, Tnf-α, Ptgs2, and Rankl (qPCR). Protein levels of TGF-β and IL-10 in the tissues were determined by enzyme-linked immunosorbent assays (ELISA) or by MMP-13 and p38 immunoblot. Results: Silencing Mmp-13 expression reduced bone resorption significantly. Expression of Mmp-13, Il-6, and Tnf-α, as well as the protein levels of IL-6 and TNF-α, was reduced in the animals treated with adenovirus-delivered shRNA; however, these effects were not associated with modulation of p38 MAPK signaling. Interestingly, inhibition Mmp-13 did not affect the severity of inflammatory infiltrate. Conclusions: Site-specific inhibition of MMP-13 reduced bone resorption and production of inflammatory mediators associated with periodontal disease. Clinical relevance: The results suggest that site-specific inhibition of MMP-13 may be an interesting strategy to modulate inflammation and reduce bone resorption in osteolytic inflammatory diseases.
Keywords: Bone resorption; Inflammation; Lipopolysaccharide; Metalloproteinase-13; Periodontal disease